Swelling Among Women Who Need Education About Leg Lymphedema: A Descriptive Study of Lymphedema in Women Undergoing Surgery for Endometrial Cancer. Issue 8 (1st October 2014) - Salani, Ritu; Preston, Megan M.; Hade, Erinn M.; Johns, Jessica; Fowler, Jeffrey M.; Paskett, Electra P.; Katz, Mira L.
Abstract : Objectives: In addition to hysterectomy and bilateral salpingo-oophorectomy, comprehensive surgical staging for endometrial cancer includes pelvic and para-aortic lymphadenectomy. Clarifying and addressing the morbidity from these surgical procedures is imperative. The goal of this study was to assess the prevalence of lower extremity swelling after surgery for endometrial cancer. Materials and Methods: We performed a descriptive, cross-sectional survey study of women who underwent surgery for endometrial cancer at our institution from 2006 to 2008. Survey information included symptoms, management, and education regarding lymphedema. Demographic information such as race and education was collected in addition to clinical data such as body mass index and age. Results: Of the 482 patients identified, 440 were determined eligible and 305 (69.3%) responded to the survey with information on lower limb swelling (LLS). Of the 108 (35%) responders who reported swelling, only 68 (22%) participants reported a diagnosis of lower limb lymphedema (LLL). The most commonly experienced symptoms among those who reported LLS were tightness, pain/tenderness, and heaviness. Among those with a diagnosis of LLL, most (60%) stated it affected their daily activities and noted exacerbating factors such as prolonged standing, heat, and walking. The most common therapies used to reduce symptoms included leg elevation (96%), compression stockings (65%), diuretics (46%), massage therapy (35%), and bandaging (25%). There was no association between LLS or LLL diagnosis and body mass index, age, race, and tobacco use. Only 8% of responders reported receiving preoperative education regarding risks for LLS and a desire for more comprehensive education was frequently noted. Conclusions: The patient-reported incidence of LLS occurred in approximately 35% of survey participants who underwent surgery for endometrial cancer. However, only 22% reported a diagnosis of LLL. Efforts to obtain the true incidence of LLL and to develop effective educational materials and programs to improve the management of lymphedema are warranted.